Criminal liability for crimes committed with public display and publicly displayed work - Olga Yu. Savelyeva (Jus Strictum, 2025)
The choice of the topic of this paper is caused by the growing number of cases of public and demonstrative commission of crimes using mass media and the Internet, which is reflected in the activities on editing criminal legislation norms, aimed at increasing the effectiveness of the fight against these socially dangerous phenomena. This study is aimed at comparing and analyzing the concepts of public display and publicly displayed work to identify similarities and differences between these terms, developing recommendations for their correct application in the qualification of crimes in law enforcement activities, as well as making proposals to amend the criminal legislation. The results of the study show that the concepts of public display and publicly displayed work differ significantly in their content and belonging to the signs of the objective side of the crime. Public display of a work involves showing on the screen the created final product, such as a film or audio composition, while public display is more often associated with a live stream in real time using certain digital means (websites, etc.). It has been found that the term “work” is covered by civil legislation and includes various types of intellectual activity. In turn, the definition of public display is an exclusively criminal-legal category. A comprehensive study of the criminal-legal norms of the Special Part of the Criminal Code of the Russian Federation allowed concluding that even if it is impossible to impute an attribute related to public display, qualification according to another independent attribute related to the use of mass media and the Internet is not excluded. A number of gaps in the legal regulation of liability for individual criminal acts that may be associated with public display have been identified.